An open-source web mapping tool to estimate wind energy in the Iberian Peninsula. Issue 1 (2nd January 2019) - Gomariz-Castillo, Francisco; Alonso-Sarría, Francisco; Pedro Montávez, Juan; Lorente-Plazas, Raquel
Abstract: The main disadvantage of wind energy is its high spatial and temporal variability. This paper presents a web mapping tool to communicate to private users both the available wind resource and information to evaluate the suitability of several types of turbine for any point on the Iberian Peninsula. This tool performs on-the-fly three-dimensional interpolation of wind data from a 10 km horizontal grid database previously obtained using a regional climate model and generates a PDF report. It integrates several open-source GIS applications to build a coherent platform that performs advanced calculations and provides graphics and reports of high quality.